The Accessibility of Opioid Agonist Treatment and Its Forced Discontinuation in Swiss Prisons—Attitudes, Perceptions and Experiences of Defense Lawyers in Dealing With Detained Persons Using Opioids - Buadze, Anna; Baggio, Stephanie; Schleifer, Roman; Aeberhard, Eveline; Wolff, Hans; Schneeberger, Andres; Liebrenz, Michael (Frontiers in Psychiatry, 2020)
Background: Opioid agonist treatment (OAT) is an important pillar in the treatment of individuals using opioids and its continuation during imprisonment is recommended. Despite this knowledge access to and continuation of OAT is still limited in many countries. The forced discontinuation during pre-trial detention can cause severe withdrawal symptoms, which in turn may significantly impair the defendant’s ability to exercise granted procedural participation rights. Furthermore, it can be argued that forced discontinuation of a desired treatment represents a form of a compulsory intervention. Aims: The present study was developed against the backdrop of a recent ruling by the European Court of Human Rights (Wenner vs. Germany). It intended to examine how defense lawyers dealing with detained persons using opioids view and assess the accessibility of OAT in pre-trial detention as well as during imprisonment in different parts of Switzerland. Methods: Using a qualitative approach, we interviewed 11 defense lawyers from three different cantons of Switzerland with multiple years of experience in providing legal representation to more than 220 defendants using heroin. The interviews were analyzed with QSR NVIVO 11 for Windows. A qualitative content analysis approach was used to evaluate findings. Results: Defenders who had been exposed to the opioid crisis during the course of their legal career had adopted a positive attitude towards OAT and associated it with a stabilizing influence on their clients, an improvement in criminal prognosis, and a reduction in recidivism. They were generally of the opinion that access to OAT had improved, however identified a considerable variance in different penitentiaries, which were mediated by attitudes of staff and authorities. Based on the assessments of the defense lawyers, it can be estimated that the initiation of OAT especially during pre-trial detention is challenging. The predominant aim of OAT in a variety of Swiss prisons still seems to focus on a discontinuation, mediated by a forced reduction of medication. Some of the interventions reported are not in line with the principle of equivalence and strongly contrast the recommendations of the Council of Europe.